Crecimiento, sobrevivencia y estado fitosanitario en una plantación de Cedrelinga cateniformis del CIEFOR – Puerto Almendra, Loreto – Perú. 2022 - Guevara Cárdenas, Lenner Henry (2023)
The study was carried out in Plot No. 12 of the canopy plantation of Cedrelinga cateniformis located in CIEFOR – Puerto Almendra. The objective was to determine the growth, survival and quality of the seedlings planted in 2020. The V. sebifera plantation reached an average increase in diameter of 1.06 mm. Regarding height, the average increase of the plantation was 10.83 cm. Surviving plants totaled 70.5% of the total (141 live plants), while mortality reached 29.5% (59 dead plants). Similarly, the V. sebifera plantation presented the highest number of plants with GOOD quality with a total of 104 seedlings representing 73.8% of the total, followed by REGULAR quality with 29 seedlings representing 20.6%. and, with BAD quality, it was obtained by 8 seedlings, which represented 5.7% of the total. According to the analysis of variance, there is a statistical difference in the increase in height of Cedrelinga cateniformis and the evaluation bands (p=0.03). Continue with the biometric evaluations of the V. sebifera plantation and carry out similar studies with other promising forest species in CIEFOR - Puerto Almendra.